The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12884-023-05451-6
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note: The effect of uterine artery ligation in patients with central placenta pevia: a randomized controlled trial

Abstract: This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12884-018-1989-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, IIAL also has high failure rates. BUAL is the initial stage in a uterine devascularization strategy that can control bleeding in PPH patients, and it could be used prophylactically to minimize the incidence of PPH in high-risk cases with a high success rate and low risk of complications [17] . Our study showed that artery diameters measurements and blood flow by color doppler enhanced after one week, 6 months and12 months compared to the 1st measurements after one day.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IIAL also has high failure rates. BUAL is the initial stage in a uterine devascularization strategy that can control bleeding in PPH patients, and it could be used prophylactically to minimize the incidence of PPH in high-risk cases with a high success rate and low risk of complications [17] . Our study showed that artery diameters measurements and blood flow by color doppler enhanced after one week, 6 months and12 months compared to the 1st measurements after one day.…”
Section: Discussionmentioning
confidence: 99%